Polygraphies : Francophone women writing Algeria - Rice, Alison, 1973- (University of Virginia Press, 2012)
"Coinciding with the fiftieth anniversary of Algeria's independence, Polygraphies is significant and timely in its focus on autobiographical writings by seven of the most prominent francophone women writers from Algeria today, including Maïssa Bey, Hélène Cixous, Assia Djebar, and Malika Mokeddem. These authors witnessed both the "before" and "after" of the colonial experience in their land, and their fictional and theoretical texts testify to the lasting impact of this history. From a variety of personal perspectives and backgrounds, each writer addresses linguistic, religious, and racial issues of crucial contemporary importance in Algeria. Alison Rice engages their work from a range of disciplines, striving both to heighten our sensitivity to the plurality inherent in their texts and to move beyond a true/false dichotomy to a wealth of possible truths, all communicated in writing."--Project Muse.